Porous carbon material, silicon-carbon negative electrode material, and preparation method and application thereof

CN122950486APending Publication Date: 2026-10-20HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611175132.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0003]然而,硅负极在实际应用中面临重大挑战,主要是由于其在锂化过程中体积膨胀大,导致机械应力和电极退化

Benefits of technology

[0027]本发明的锂离子电池由于采用了高强度、合理孔径分布的多孔碳材料或由其制备的硅碳负极材料,具有高比容量、优异的循环稳定性和低电极膨胀率等优点,适用于高比能储能设备。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention discloses a porous carbon material, a silicon-carbon anode material, its preparation method, and its applications, relating to the field of lithium-ion battery materials technology. The porous carbon material is a composite carbon matrix, comprising a first-phase carbon and a second-phase carbon; the first-phase carbon includes phenolic resin-based carbon materials, and the second-phase carbon includes lignin-based carbon materials; the porous carbon material has a hierarchical porous structure, including micropores and mesopores. The preparation method of the porous carbon material includes: mixing and curing phenolic resin, lignin, a curing agent, and a pore-forming agent, followed by carbonization and activation treatment. The porous carbon material of this invention possesses a high-strength carbon framework and a reasonable micro-to-mesopore ratio, effectively buffering the volume expansion of silicon during charge and discharge. When used in silicon-carbon anode materials, it exhibits excellent cycle stability and high initial coulombic efficiency, with a capacity retention rate exceeding 91% after 1000 cycles and a full-electrode sheet expansion rate as low as 32.6%, making it suitable for high-energy-density lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery materials technology, specifically to porous carbon materials, silicon-carbon anode materials, their preparation methods, and applications. Background Technology

[0002] Currently, among lithium-ion battery anode materials, apart from graphite, silicon is one of the most promising anode materials due to its high theoretical capacity (4200 mAh / g) and low discharge potential (0.06V vs. Li / Li+).

[0003] However, silicon anodes face significant challenges in practical applications, primarily due to their large volume expansion during lithiation, leading to mechanical stress and electrode degradation. Furthermore, the instability of the solid electrolyte interface (SEI) during cycling results in continuous consumption of active materials and a sustained decline in coulombic efficiency. To address these challenges, vapor-deposited silicon-carbon (CVD) has gradually entered the market in recent years. This CVD method, based on silane gas, can deposit uniform nano-silicon on a carbon matrix scaffold. Surface modification through coating layers can alleviate the volume expansion of silicon-carbon materials. The main technologies of this method include using carbon nanotubes (CNTs), graphite, and activated carbon as carbon matrix scaffolds. Among various porous materials, activated carbon offers better control over its specific surface area, pore volume, and pore size. Activated carbon sources mainly include resin-based, biomass, and coke-based materials. However, currently, activated carbon materials exhibit low compaction, low matrix strength, and poor resistance to expansion. Therefore, silicon-carbon materials prepared using this method have low strength, and the particles are easily broken during the rolling process of preparing anode sheets. Further improvements are needed in material expansion and cycling stability.

[0004] Therefore, improving the strength of porous carbon materials, enhancing their resistance to expansion, and improving the cycle stability of silicon-carbon materials in batteries are urgent problems to be solved in this field. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of existing technologies and provide porous carbon materials, silicon-carbon anode materials, their preparation methods, and applications. The specific technical solution of this invention is as follows: In a first aspect, the present invention provides a porous carbon material, wherein the porous carbon material is a composite carbon matrix comprising a first phase carbon and a second phase carbon; the first phase carbon comprises a phenolic resin-based carbon material, and the second phase carbon comprises a lignin-based carbon material; the porous carbon material has a hierarchical pore structure, wherein the hierarchical pore structure comprises micropores and mesopores.

[0006] This invention uses phenolic resin and lignin as two-phase carbon precursors. During curing, these two components undergo a cross-linking reaction to form a composite precursor with an interpenetrating network structure. After carbonization, a composite carbon matrix is ​​obtained that combines a rigid framework with a toughening reinforcing phase. Compared to single-precursor carbon materials, this significantly improves the compressive strength of porous carbon materials. Simultaneously, this porous carbon material possesses a rational microporous and mesoporous hierarchical structure. The micropores provide high specific surface area and silicon storage sites, while the mesopores provide silicon deposition space and lithium-ion transport channels, which helps alleviate the volume expansion of silicon during charge and discharge, thereby improving the cycle stability of silicon-carbon anode materials.

[0007] Furthermore, based on a total pore volume of 100%, the proportion of micropores is 50% to 95%, and the proportion of mesopores is 5% to 50%; wherein, based on a total pore volume of 100%, the proportion of ultramicropores is ≤20%.

[0008] In this invention, ultramicropores refer to pores with a diameter less than 0.7 nm, micropores refer to pores with a diameter less than 2 nm (including ultramicropores), and mesopores refer to pores with a diameter between 2 nm and 50 nm. By controlling the appropriate ratio of micropores and mesopores, especially by controlling the proportion of ultramicropores to not be too high, the problem of silane gas being unable to enter the pores and deposit due to excessively small pore sizes can be avoided, while ensuring sufficient mesopore volume to accommodate silicon material and buffer volume expansion.

[0009] Furthermore, taking the total pore volume as 100%, the proportion of micropores is 80% to 88%, and the proportion of mesopores is 12% to 20%; wherein, the proportion of the pore volume of the ultramicropores to the total pore volume is ≤15%.

[0010] Furthermore, the porous carbon material has a particle size Dv50 of 2–30 μm, a specific surface area of ​​500–3000 m² / g, and a pore volume of 0.4–2.0 cm³ / g. By controlling these parameters, the porous carbon material is ensured to possess both sufficient silicon storage space and active sites, as well as good processing performance and electrode forming performance.

[0011] Furthermore, the compaction density of the porous carbon material under 350 MPa pressure is 0.80–1.05 g / cm³, and the compaction change rate is 20%–50%. The high compaction density and low compaction change rate reflect the high structural strength of the carbon skeleton of the porous carbon material, making it less prone to breakage during the subsequent negative electrode rolling process, while effectively resisting the expansion stress during the silicon lithium intercalation process.

[0012] Secondly, the present invention provides a method for preparing the above-mentioned porous carbon material, the method comprising the following steps: S1. Mix the first-phase carbon precursor, the second-phase carbon precursor, the curing agent and the pore-forming agent evenly, and heat to cure to obtain the composite precursor. S2. The composite precursor is heated and carbonized under a protective atmosphere to obtain a composite carbon material. S3. The composite carbon material is crushed, heated under a protective atmosphere, and activated by passing in an activation gas to obtain a porous carbon material.

[0013] This method first forms a composite precursor with an interpenetrating network structure through the synergistic curing of phenolic resin and lignin. Then, it utilizes the pyrolysis and volatilization of a pore-forming agent during carbonization to construct preliminary pores. Finally, it precisely controls the pore structure through secondary activation to form a multi-level porous carbon material with high strength and reasonable pore size distribution.

[0014] Further, in step S1, the first phase carbon precursor is a phenolic resin, which includes at least one of phenol-formaldehyde resin, cresol-formaldehyde resin, xylenol-formaldehyde resin, and bisphenol A phenolic resin; the second phase carbon precursor is lignin, which includes at least one of alkaline lignin, enzymatically hydrolyzed lignin, and sodium lignin sulfonate; the mass ratio of the first phase carbon precursor to the second phase carbon precursor is 1:(0.2~5).

[0015] Phenolic resin provides a rigid carbon skeleton, while lignin, as a carbon precursor from biomass, has abundant oxygen-containing functional groups that can undergo condensation reactions with the hydroxymethyl groups of phenolic resin, enhancing the interfacial bonding between the two phases and improving the structural strength of the carbon matrix after carbonization. Within the above-mentioned mass ratio range, the optimal balance between rigidity and toughness can be achieved. If the amount of lignin added is too low, the reinforcing effect is not obvious; if the amount added is too high, the rigidity of the carbon skeleton decreases.

[0016] Furthermore, in step S1, the curing agent is at least one of hexamethylenetetramine, trimethylhexamethylenediamine, and diethylaminopropylamine; the mass of the curing agent is 2-20 wt% of the total mass of the first precursor and the second precursor. An appropriate amount of curing agent can promote the cross-linking and curing reaction of phenolic resin and lignin, forming a three-dimensional network structure and improving the mechanical properties of the carbonized carbon material.

[0017] Furthermore, in step S1, the pore-forming agent is polyethylene glycol (PEG), with a molecular weight of 200–20000, and the amount of PEG added is 5–150 wt% of the total mass of the first and second precursors. During carbonization, PEG undergoes complete pyrolysis and volatilization, leaving interconnected pores. Its molecular weight affects the pore-forming effect: lower molecular weight PEG is conducive to the formation of micropores, while higher molecular weight PEG is conducive to the formation of mesopores. By controlling the amount and molecular weight of PEG added, the pore structure can be initially regulated.

[0018] Furthermore, in step S1, the heating and curing temperature is 80–300°C, the heating rate is 0.5–5°C / min, and the curing time is 0.5–20 h.

[0019] Furthermore, in step S2, the protective atmosphere is selected from one or more of nitrogen, argon, helium, neon, and krypton; the heating temperature is 500–1200°C, and the time is 0.5–20 h. Within the above temperature range, the precursor is fully carbonized to form a carbon skeleton with a certain degree of graphitization and mechanical strength.

[0020] Furthermore, in step S3, the activating gas is at least one of water vapor, carbon dioxide, oxygen, and air; the flow rate of the activating gas is 1–30 L / min; the activation temperature is 500–1200 °C, and the activation time is 0.5–20 h. By controlling the activation conditions, the ratio of micropores to mesopores can be precisely adjusted, resulting in a reasonable pore size distribution in the final porous carbon material, which is beneficial for the diffusion of silane gas and the uniform deposition of silicon material.

[0021] Thirdly, the present invention provides a silicon-carbon anode material comprising: a core, the core comprising the porous carbon material described in the first aspect above and silicon material located in the pores of the porous carbon material; and a coating layer formed on the surface of the core, the coating layer being a carbon layer.

[0022] This silicon-carbon anode material uses high-strength, multi-level porous carbon material as a framework, with nano-silicon deposited inside the pores. The surface carbon coating layer further blocks the direct contact between the electrolyte and silicon, reducing side reactions and improving cycle stability.

[0023] Furthermore, in the silicon-carbon anode material, the silicon content is 30-70 wt%, and the carbon content is 30-70 wt%. Within the above silicon content range, both high specific capacity and the effective buffering effect of the porous carbon framework and carbon coating layer on silicon expansion can be ensured.

[0024] Fourthly, the present invention provides a method for preparing the above-mentioned silicon-carbon anode material, the method comprising the following steps: Provide the porous carbon material described in the first aspect above; The porous carbon material is placed in a deposition apparatus and heated to 400-600°C under a protective atmosphere. A silicon source gas is introduced to perform vapor phase deposition, so that silicon material is deposited in the pores of the porous carbon material to obtain a silicon-loaded porous carbon material. The silicon-supported porous carbon material is heated to 500-700°C under a protective atmosphere, and a carbon source gas is introduced for gas-phase coating to form a carbon coating layer on the surface of the silicon-supported porous carbon material, thereby obtaining a silicon-carbon anode material.

[0025] This preparation method involves uniformly depositing silicon in the form of nanoparticles into the pores of porous carbon material via vapor deposition, and then coating the surface with vapor to form a dense carbon layer. The process is simple and controllable, making it suitable for industrial production.

[0026] Fifthly, the present invention provides a lithium-ion battery comprising the porous carbon material described in the first aspect or the silicon-carbon anode material described in the third aspect.

[0027] The lithium-ion battery of the present invention has advantages such as high specific capacity, excellent cycle stability and low electrode expansion rate due to the use of porous carbon materials with high strength and reasonable pore size distribution or silicon-carbon anode materials prepared therefrom, and is suitable for high specific energy storage devices.

[0028] Compared with the prior art, the beneficial technical effects of this invention are reflected in: (1) The present invention forms a composite carbon matrix with an interpenetrating network structure by synergistic curing of phenolic resin and lignin dual-phase carbon precursor, which has both a rigid carbon skeleton and a tough reinforcing phase. Compared with single precursor carbon materials, it significantly improves the compressive strength and anti-pulverization ability of porous carbon materials.

[0029] (2) This invention combines PEG pore-forming agent pyrolysis volatilization pore-forming and secondary gas activation pore-forming to achieve precise control of the micropore and mesopore ratio of porous carbon materials, and obtain a reasonable multi-level pore structure, which provides sufficient silicon deposition space and ensures good lithium ion transport channels.

[0030] (3) The silicon-carbon anode material prepared by the porous carbon material of the present invention has high initial coulombic efficiency, low electrode expansion rate and excellent long cycle stability, which effectively solves the problems of large volume expansion and poor cycle stability of silicon-carbon anode material. Attached Figure Description

[0031] Figure 1 This is a SEM image of the porous carbon material provided in Embodiment 1 of the present invention.

[0032] Figure 2 The diagram shows the full-cell cycle performance of a silicon-carbon anode material provided in Embodiment 1 of the present invention. Detailed Implementation

[0033] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.

[0034] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0035] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that excludes other embodiments. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0036] The embodiments of the present invention will be described in detail below with reference to the accompanying drawings.

[0037] Example 1 A method for preparing porous carbon materials includes the following steps: S1. Phenolic formaldehyde resin, which serves as the first phase carbon precursor, and alkaline lignin, which serves as the second phase carbon precursor, are mixed at a mass ratio of 1:1 (total 2 kg). Then, 8 wt% of hexamethylenetetramine, which accounts for the total mass of the first and second phase carbon precursors, is added as a curing agent (0.16 kg). 50 wt% of polyethylene glycol with a molecular weight of 1000, which accounts for the total mass of the first and second phase carbon precursors, is added as a pore-forming agent (1 kg). After mixing evenly, the mixture is placed in an oven and heated to 180°C in air at a rate of 0.5°C / min. The temperature is maintained for 10 hours to obtain the composite precursor.

[0038] S2. Place the composite precursor in a high-temperature furnace and heat it to 800℃ under nitrogen protection. Hold the temperature for 3 hours with a nitrogen gas flow rate of 10L / min to perform carbonization treatment, which causes the polyethylene glycol to pyrolyze and volatilize to form pores, thus obtaining the composite carbon material.

[0039] S3. 2 kg of composite carbon material was crushed and classified. The particle size Dv50 after crushing was 9.2 μm. The material was placed in a fluidized bed activation device and heated to 850℃ under nitrogen protection. Water vapor was introduced for activation. The water vapor flow rate was 3 L / min (i.e., 1.5 L / (min·kg)) and the nitrogen flow rate was 12 L / min. The temperature was kept constant for 2 hours. After cooling, the material was discharged to obtain porous carbon material with a Dv50 of 7.4 μm.

[0040] Preparation method of silicon-carbon anode material: S4. Place 1 kg of the porous carbon material prepared in step S3 above into a fluidized bed deposition apparatus, heat it to 500°C under nitrogen protection, and introduce silane gas for vapor phase deposition. The silane flow rate is 3 L / min, and the deposition time is 4 h, so that nano-silicon is deposited in the pores of the porous carbon material to obtain silicon-supported porous carbon material. After the silane deposition is at a constant temperature, continue to heat it to 550°C, and introduce acetylene gas as a carbon source. The acetylene flow rate is 3 L / min, and the gas introduction time is 4 h, so that a carbon coating layer is formed on the surface of the silicon-supported porous carbon material to obtain silicon-carbon anode material.

[0041] Figure 1 This is a scanning electron microscope (SEM) image of a porous carbon material provided in Embodiment 1 of the present invention. Figure 1 As can be seen, this porous carbon material exhibits an irregular, dense, blocky particle morphology with a rough particle surface and numerous micropores. Combined with the test data in Table 1 (particle size Dv50 is 7.4 μm, and it possesses extremely high specific surface area and a micro-mesoporous hierarchical structure), this demonstrates its superior properties. Figure 1 The morphological characteristics directly reflect the well-developed porous network formed inside and on the surface of the material by polyethylene glycol (PEG) pore formation and secondary gas activation. This structure not only has high mechanical strength, but also provides sufficient internal space and attachment sites for subsequent silane vapor deposition, which is conducive to the uniform deposition and embedding of nano-silicon particles in the porous carbon matrix, thereby effectively buffering the huge volume expansion of silicon during charging and discharging from the source.

[0042] Figure 2 This is a cycle performance curve of the silicon-carbon anode material prepared in Example 1 of the present invention in a pouch cell. From... Figure 2 As can be seen, under the conditions of 25℃, 2.5–4.25V voltage range, and high-rate charge / discharge testing at 1C / 1C, the battery exhibits excellent long-cycle stability. Throughout the entire 1000-cycle process, the capacity retention curve shows a very gradual decline. After 1000 charge-discharge cycles, its capacity retention remains as high as 91.4%, completely avoiding the capacity drop or rapid decay commonly seen in conventional silicon-carbon anode materials. This further confirms that the carbon skeleton prepared by cross-linking and curing phenolic resin and lignin in this invention possesses excellent compressive strength and structural rigidity. Combined with a reasonable hierarchical porosity, it successfully suppresses the pulverization of the active material silicon and the continuous cracking of the solid electrolyte interface (SEI) during cycling, significantly extending the service life of the silicon-carbon anode material in lithium-ion batteries.

[0043] Example 2 The difference between this embodiment and Embodiment 1 is that in step S1, the alkaline lignin, which serves as the second-phase carbon precursor, is replaced with enzymatically hydrolyzed lignin, and the mass ratio of phenol-formaldehyde resin to enzymatically hydrolyzed lignin is 1:3. The remaining steps and parameters are the same as in Embodiment 1.

[0044] Example 3 The difference between this embodiment and Embodiment 1 is that in step S1, polyethylene glycol with a molecular weight of 1000 is replaced with polyethylene glycol with a molecular weight of 4000. The remaining steps and parameters are the same as in Embodiment 1.

[0045] Example 4 The difference between this embodiment and Embodiment 1 is that in step S2, the temperature is raised to 900°C under nitrogen protection and held at that temperature for 2 hours. The remaining steps and parameters are the same as in Embodiment 1.

[0046] Comparative Example 1 The difference between this comparative example and Example 1 is that in step S1, the alkaline lignin is replaced with an equal mass of phenol-formaldehyde resin, that is, phenol-formaldehyde resin is used entirely as the precursor, and no lignin is added. The remaining steps and parameters are the same as in Example 1.

[0047] Comparative Example 2 The difference between this comparative example and Example 1 is that polyethylene glycol (PEG) pore-forming agent is not added in step S1. That is, only phenol-formaldehyde resin and alkaline lignin are mixed at a mass ratio of 1:1 (2 kg in total), and then hexamethylenetetramine (0.16 kg) accounting for 8 wt% of the total mass of the first phase carbon precursor and the second phase carbon precursor is added as a curing agent. PEG is not added. The remaining curing steps are the same as in Example 1. In step S2, the composite precursor is placed in a high-temperature furnace and heated to 800°C under nitrogen protection. The temperature is maintained for 3 hours with a nitrogen gas flow rate of 10 L / min for carbonization. Since no PEG is added, there is no polyethylene glycol pyrolysis volatilization to create pores during the carbonization process, thus obtaining the composite carbon material. Step S3 and subsequent steps are the same as in Example 1.

[0048] Comparative Example 3 The difference between this comparative example and Example 1 is that the secondary activation with water vapor in step S3 is not performed. Instead, the composite carbon material prepared in step S2 is directly used as a porous carbon material after being crushed and classified, without water vapor activation treatment. The subsequent step S4 is the same as in Example 1.

[0049] Performance testing The porous carbon materials and silicon-carbon anode materials prepared in the examples and comparative examples were subjected to performance tests, and the test methods are as follows: (1) A fully automatic specific surface area and pore size analyzer (Autosorb-iQ, USA) was used. Nitrogen adsorption-desorption test was used, and the pore volume, ultra-micropore ratio, micropore ratio, mesopore ratio and specific surface area of ​​porous carbon materials and silicon-carbon anode materials were measured by fitting analysis using the NLDFT model.

[0050] In this invention, the pore size classification is defined as follows: Micropores: pores with a diameter of less than 0.7 nm; Micropores: refer to pores with a diameter of less than 2 nm, including ultramicropores; Mesopores: pores with a diameter between 2nm and 50nm.

[0051] (2) The particle size Dv50 of porous carbon materials and silicon-carbon anode materials was measured using a laser particle size analyzer (Malvin Panaco, 3000).

[0052] (3) Use a compaction tester to test compaction at pressures of 10~350MPa and calculate the compaction change rate. Starting from the compaction density at 10MPa pressure, calculate the compaction change rate according to the following formula: For example, the change rate of powder at 350MPa = (compaction density at 350MPa - compaction density at 10MPa) / compaction density at 10MPa × 100%.

[0053] (4) The carbon content in the silicon-carbon anode material was determined using a carbon-sulfur analyzer (Lico, CS844, USA); the silicon content was tested using thermogravimetric analysis (TGA) by heating to 1100℃ in air and calculating the silicon content using the following formula: Si (wt%) = 100 × [M 1100 ×[28 / (28+(16×2)] / M0], where M 1100 M0 is the mass at 1100℃, and M0 is the initial mass.

[0054] (5) Button cell electrochemical test: The silicon-carbon anode material, conductive carbon black and binder LA133 were mixed in a ratio of 8:1:1 to form a slurry, which was then uniformly coated onto copper foil. After drying, the anode sheet was prepared and assembled with the counter electrode lithium sheet, separator and electrolyte to form a button cell. Its electrochemical performance was tested on the Xinwei Battery Test Cabinet. The charge and discharge regime was as follows: the battery was left to stand for 10 hours, discharged at 0.1C to 0.005V, discharged at 0.05C to 0.005V, and charged at 0.1C to 1.5V.

[0055] (6) Full battery performance test: Negative electrode preparation: The negative electrode slurry formulation has the following mass ratio: silicon-carbon negative electrode material: artificial graphite: conductive carbon black (SP): carbon nanotubes (CNTs): polyacrylic acid (PAA): styrene-butadiene rubber (SBR) = 18.5:74:1.9:0.1:4.4:1.1. This slurry is then uniformly coated onto copper foil, dried, and rolled to a density of 1.6 g / cm³. 3The negative electrode sheet is compacted and prepared. The prepared negative electrode sheet is then assembled with the positive NCM88 electrode sheet, separator, and electrolyte into a pouch cell. After stacking and assembly, it is placed in an aluminum-plastic film casing for encapsulation, baked, and then filled with electrolyte, followed by formation and capacity testing. The battery is then tested at 25°C under a charging / discharging regime of 1C, with a voltage range of 2.5–4.25V.

[0056] The test results are shown in Tables 1 and 2.

[0057] Table 1. Performance test results of materials prepared in different embodiments and comparative examples.

[0058] Note: The sum of the micropore and mesopore proportions in each embodiment and comparative example in Table 1 is not always equal to 100%. This is because some samples also contain a very small amount of macropores with a pore size >50 nm, which do not significantly affect the overall performance of the material. The porous carbon material of the present invention features micropores and mesopores as its main pore structure characteristics.

[0059] As can be seen from the data in Table 1, the porous carbon materials prepared in Examples 1-4 have higher compaction densities (0.94-0.96 g / cm³ in Examples 1-4, 0.77 g / cm³ in Comparative Example 1) and smaller compaction variation rates (33.9%-35.1% in Examples 1-4, 53.2% in Comparative Example 1). This indicates that the present invention significantly improves the strength of the porous carbon matrix through the synergistic effect of phenolic resin and lignin dual-phase precursor, which is beneficial for subsequent silane deposition to embed silicon materials into the pores and alleviate the volume expansion of silicon.

[0060] As can be seen from the data in Table 1, the porous carbon materials prepared in Examples 1-4 have significantly higher specific surface area and pore volume compared to Comparative Example 2. This indicates that the volatilization of PEG during carbonization provides the necessary basic pores for subsequent silicon deposition. Without the initial activation of PEG to create pores, secondary activation alone is not effective.

[0061] As can be seen from the data in Table 1, compared with Comparative Example 3, the porous carbon materials prepared in Examples 1-4 have higher specific surface area and pore volume, and a more reasonable proportion of micropores. This indicates that the pore volume created by PEG alone is insufficient and the proportion of micropores is too high. Secondary activation is the key step to control the final micropore and mesopore ratio and ensure high specific surface area and high pore volume.

[0062] Table 2 Electrochemical performance test results of silicon-carbon anode materials prepared in different embodiments and comparative examples

[0063] As can be seen from the data in Table 2, compared with Comparative Example 1, Examples 1-4 have higher initial coulombic efficiency, significantly reduced full-charge electrode expansion, and better 1000-cycle retention rate. This indicates that the porous carbon skeleton formed by the two-phase precursor has higher strength, and the silicon material present in the pores can effectively alleviate the expansion of the material and improve the cycling performance of the material.

[0064] As can be seen from the data in Table 2, Examples 1-4, compared to Comparative Example 2, exhibited higher initial coulombic efficiency, lower expansion, and better cycle performance. This indicates that the absence of PEG and the lack of basic pore formation hinders subsequent silicon deposition, resulting in poor electrical performance. Compared to Comparative Example 3, Examples 1-4 lacked secondary activation to regulate the ratio of micropores to mesopores in the porous carbon, leading to lower pore volume, a higher proportion of micropores, and insufficient porosity in silicon deposition. This resulted in lower initial efficiency, poorer expansion, and poorer cycle performance of the silicon-carbon material. In summary, the rich pore structure formed by the combined effects of PEG pore-forming and secondary activation is beneficial for subsequent silicon deposition and buffering expansion, while the absence of either step leads to significant degradation in electrical performance.

[0065] The above detailed description is a specific description of one of the feasible embodiments of the present invention. This embodiment is not intended to limit the patent scope of the present invention. All equivalent implementations or modifications that do not depart from the present invention should be included within the scope of the technical solution of the present invention.

[0066] It should be particularly noted that the various embodiments listed in this specification and accompanying drawings are intended to illustrate the technical solutions and advantages of the present invention, and not to limit the scope of protection of the present invention. Without departing from the core ideas and technical effects of the present invention, those skilled in the art can make any form of improvement, substitution, combination, or modification to the structural arrangement, process parameters, material selection, control logic, etc., of the described embodiments; any obvious changes based on the same concept should be considered equivalent solutions of the present invention and should be included within the scope of protection defined by the claims of the present invention. The actual scope of protection of the present invention is determined by the appended claims and should be correctly understood in conjunction with the specification and accompanying drawings.

Claims

1. A porous carbon material, characterized in that, The porous carbon material is a composite carbon matrix, comprising a first phase carbon and a second phase carbon; the first phase carbon comprises phenolic resin-based carbon material, and the second phase carbon comprises lignin-based carbon material; the porous carbon material has a hierarchical pore structure, which includes micropores and mesopores.

2. The porous carbon material according to claim 1, characterized in that, With the total pore volume as 100%, the proportion of micropores is 50% to 95%, and the proportion of mesopores is 5% to 50%; wherein, with the total pore volume as 100%, the proportion of ultramicropores is ≤20%.

3. The porous carbon material according to claim 1, characterized in that, The porous carbon material has a particle size Dv50 of 2–30 μm, a specific surface area of ​​500–3000 m² / g, and a pore volume of 0.4–2.0 cm³ / g.

4. The porous carbon material according to claim 1, characterized in that, The porous carbon material has a compaction density of 0.80–1.05 g / cm³ under 350 MPa pressure, and a compaction change rate of 20%–50%.

5. A method for preparing a porous carbon material as described in claim 1, characterized in that, Includes the following steps: S1. Mix the first-phase carbon precursor, the second-phase carbon precursor, the curing agent and the pore-forming agent evenly, and heat to cure to obtain the composite precursor. S2. The composite precursor is heated and carbonized under a protective atmosphere to obtain a composite carbon material. S3. The composite carbon material is crushed, heated under a protective atmosphere, and activated by passing in an activation gas to obtain a porous carbon material.

6. The preparation method according to claim 5, characterized in that, In step S1, the first phase carbon precursor is a phenolic resin, which includes at least one of phenol-formaldehyde resin, cresol-formaldehyde resin, xylenol-formaldehyde resin, and bisphenol A phenolic resin. The second phase carbon precursor is lignin, which includes at least one of alkaline lignin, enzymatically hydrolyzed lignin, and sodium lignin sulfonate. The mass ratio of the first phase carbon precursor to the second phase carbon precursor is 1: (0.2~5).

7. The preparation method according to claim 5, characterized in that, In step S1, the curing agent is at least one of hexamethylenetetramine, trimethylhexamethylenediamine, and diethylaminopropylamine; The mass of the curing agent is 2 to 20 wt% of the total mass of the first precursor and the second precursor.

8. The preparation method according to claim 5, characterized in that, In step S1, the pore-forming agent is polyethylene glycol with a molecular weight of 200 to 20,000, and the amount of polyethylene glycol added is 5 to 150 wt% of the total mass of the first precursor and the second precursor.

9. The preparation method according to claim 5, characterized in that, In step S1, the heating and curing temperature is 80~300℃, the heating rate is 0.5~5℃ / min, and the curing time is 0.5~20h.

10. The preparation method according to claim 5, characterized in that, In step S2, the protective atmosphere is selected from one or more of nitrogen, argon, helium, neon and krypton; the heating temperature is 500~1200℃ and the time is 0.5~20h.

11. The preparation method according to claim 5, characterized in that, In step S3, the activating gas is at least one of water vapor, carbon dioxide, oxygen, and air; the flow rate of the activating gas is 1~30 L / min; the activation temperature is 500~1200℃, and the activation time is 0.5~20 h.

12. A silicon-carbon anode material, characterized in that, include The core comprises the porous carbon material according to any one of claims 1-4 and silicon material located in the pores of the porous carbon material; And a coating layer formed on the surface of the core, the coating layer being a carbon layer.

13. The silicon-carbon anode material according to claim 12, characterized in that, The silicon-carbon anode material contains 30-70 wt% silicon and 30-70 wt% carbon.

14. A method for preparing a silicon-carbon anode material, characterized in that, Includes the following steps: Provide a porous carbon material as described in any one of claims 1 to 4; The porous carbon material is placed in a deposition apparatus and heated to 400-600°C under a protective atmosphere. A silicon source gas is introduced to perform vapor deposition, so that silicon material is deposited in the pores of the porous carbon material to obtain a silicon-loaded porous carbon material. The silicon-supported porous carbon material is heated to 500~700℃ under a protective atmosphere, and a carbon source gas is introduced for gas phase coating, forming a carbon coating layer on the surface of the silicon-supported porous carbon material to obtain a silicon-carbon anode material.

15. A lithium-ion battery, characterized in that, It includes the porous carbon material according to any one of claims 1-4 or the silicon-carbon anode material according to any one of claims 12-13.